The general equation of cosine function is:
![y=a\cos (bx+c)+d](https://img.qammunity.org/2023/formulas/mathematics/college/9fqfkgvizh0k69sfia7kctelra7c7lnwo5.png)
where:
a = amplitude
![(2\pi)/(b)=period](https://img.qammunity.org/2023/formulas/mathematics/college/7n2cx17ql22dm3vf2mwxeg1o3i1j7sj7p4.png)
![(-c)/(b)=horizontal\text{ shift}](https://img.qammunity.org/2023/formulas/mathematics/college/aeeb7i58vhghf34b9sofai5tpd0gwqogyw.png)
d = vertical shift
In this case, we have no vertical nor horizontal shifts, then:
c = 0
d = 0
The amplitude is 2, then:
a = 2
The period is 6π, then:
![\begin{gathered} (2\pi)/(b)=6\pi \\ 2\pi=6\pi\cdot b \\ (2\pi)/(6\pi)=b \\ (1)/(3)=b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1tpizm7tx7wkrsfugl6bm96go5n5ke0edv.png)
Substituting this information into the general equation, we get:
![\begin{gathered} y=2\cos ((1)/(3)x+0)+0 \\ y=2\cos ((1)/(3)x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f5zqbaps7nl08etq520hy8cjaek51bj59f.png)